Thermocapillary convection of a binary mixture with the Soret effect in a shallow annular pool heated from below. (8th October 2019) - Wu, Chun-Mei; Luo, Jia-Qian; Yu, Jia-Jia; Li, You-Rong
Abstract: In order to reveal the features of the thermocapillary convection of a binary mixture (toluene/ n -hexane mixture with an initial mass fraction of 0.2627) with the Soret effect in a shallow annular pool, a large number of unsteady numerical simulations were conducted. The shallow annular pool is heated from below with an increasing linear temperature from the inner to outer cylinders, and lateral cylinders are adiabatic. The upper free surface is open to the atmosphere. Biot ( Bi ) number varies from 0 to 2. Results indicate that the increasing Biot number enhances thermocapillary convection and has an obvious influence on the solute concentration profile generated by the Soret effect. As Biot number is increased, the solute concentration difference from the inner to outer cylinders increases; thus, the critical thermal capillary Reynolds number for the destabilization of the basic flow and the fundamental oscillation frequency near the critical point decrease. After the three-dimensional oscillatory flow appears, thermocapillary convection bifurcates continually from the hydrothermal waves to the flower patterns at a large thermal capillary Reynolds number when Bi = 0. At 0 < Bi ≤ 0.6, the flow evolves from the hydrothermal waves to chaos directly. However, at 0.6 < Bi ≤ 2, the multicellular state, the hydrothermal waves and chaos patterns appear orderly. Furthermore, the fundamental oscillation frequency rises up with the thermal capillary Reynolds number for all Biot numbers.